Distributed Fast Maximum Power Point Tracking Technique for Mismatched Module Application - M.I.M. Zakki; M.N.M. Hussain; I.R. Ibrahim; N.A. Ismail; M.N. Ibrahim (Institute of Advanced Engineering and Science, 2017)
This paper propose distributed fast maximum power point tracking (DFMPPT) technique to achieve maximum power point tracking (MPPT). This paper implements the algorithm in distributed MPPT (DMPPT) architecture for mismatched condition with single module, and string connection. The MPPT method uses indirect and direct MPPT method by fractional open-circuit voltage (FOCV) with incremental conductance (INC) for high-speed maximum energy harvesting. This method is proven to be fast for tracking maximum power point (MPP) which achieves the peak power less in 1.7ms via for a single module with efficiency of 99.7% compared to the recent MPPT technique to reach MPP in 1.75ms with 95.8% efficiency. While for string configuration, the efficiency of the whole system is rated by 85.583% by taking 8.675ms to reach global MPP.